A STUDY ON ASSAULT CASES ADMITTED TO COLOMBO SOUTH TEACHING HOSPITAL-SRI LANKA - Hulathduwa, S. R; Bandara, A. R. S. V; M. D, Aloysius (International Journal of Research -GRANTHAALAYAH, 2021)
Assault cases are commonly encountered in the day to day life of a Judicial Medical Officer or an Accident Service Surgeon. Most of the admissions to the Accident Service Unit of any major hospital in almost anywhere in the world are due to accidents and assaults. Accidents are preventable disasters and there are major organizations whose main role is to draw strategies and plans to prevent accidents. On the other hand, assaults are always man-made and the underlying factors are very different from those of accidents. Assaults are a serious health and economic burden in a country. Additionally, there are socio-economic, religious, ethnic, cultural and legal issues intermingled with the broad picture of ‘assaults’. Very few studies have been done in depth about assaults in the recent past which cover the multiple aspect of the issue. Even the conclusions drawn from the most extensive study on this subject may become obsolete and dilapidated after few years, as the patterns of wounding and the methods and trends are changing constantly across the globe. This justifies the necessity of continuous research by different authorities to this ever-changing subject. This study discusses certain demographic characters of victims, assailants, contributory factors and legal implications of assaults.